UJI ANTAGONIS KAPANG ENDOFIT DUWET (Syzigium cumini (L.) Skeels) TEHADAP KAPANG Fusarium oxysporum PENYEBAB PENYAKIT MOLER PADA BAWANG MERAH (Allium ascalonicum L.) SECARA IN-VITRO - Luthfian Nur Afifi; MG. Isworo Rukmi; Sri pujiyanto (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Endophytic fungi inhabit plant hosts for all or part of their life cycle in plant tissues without doing harm to its host. Utilization of endophytic fungi as controlling plant pathogens has been widely studied in in-vivo and in-vitro. The aims of this study was to determined the antagonistic activities of 8 endophytic fungal isolates from some parts of duwet (Syzigium cumini (L.) Skeels.) tree against F. oxysporum, a pathogenic fungi causing bulb rot disease on red onion. This study was conducted using Completely Randomized Design (CRD), with 8 endophytic fungal isolates as treatment, done in triplicates. The antagonistic activity were examined using dual culture method, by determined the percentage of inhibition. The mycelial plugs (4 mm diameter) of endophytic fungi and pathogenic fungi F. oxysporum were placed in same dish 3 cm each other. The endophytic fungal isolates were conventionally identified to genus level. The identification results showed that endophytic fungi came from 1 isolates of Aspergillus, 5 isolates of Penicillium, 1 isolate of Fusarium, and 1 isolate of Mycelia sterilia. All endophytic fungal isolates showed capability on inhabiting the growth of F. oxysporum with the percentage of inhibition varied between 1.1 to 36.0%. Fusarium JD1 isolates showed the highest antagonist activity against F. oxysporum (36.0%). Keywords : Endophytic fungi, duwet, Fusarium oxysporum, growth inhibition.